Influence of Processed Spent Bleaching Earth on the Properties of Foamed Concrete - Rokiah, Othman; Khairunisa, Muthusamy; Youventharan, Duraisamy; Mohd Arif, Sulaiman (2019)
Present research studies the effect of Processed Spent Bleaching Earth (PSBE) on the properties of foamed concrete as replacement for cement. Uses of PSBE replace cement in the proportions of 10, 20, 30 and 40 percent by weight of binder. The influences of PSBE as partial cement replacement on workability, density, compressive strength, water absorption and carbon content of foamed concrete have been reported. Results indicate that 30% PSBE significantly improved the compressive strength of foamed concrete and other properties also performed well which behaviours are comparable to normal concrete. There are fewer Ca(OH) 2 crystals and more CSH produces in 30% PSBE through SEM and XRD analysis is represent for its superior.